DRES-18. EZH2/PRC2-MEDIATED EPIGENETIC PLASTICITY PROMOTES THERAPEUTIC RESISTANCE BY REGULATING STAT3 ACTIVATION GENE NETWORK IN THE GLIOMA STEM CELLS. (6th November 2017) - Park, Cheol; Atashi, Fatemeh; Caragher, Seamus; Baisiwala, Shivani; Lesniak, Maciej S; James, C David; Ahmed, Atique
Abstract: Glioma stem cells (GSCs), a rare population of GBM cells capable of self-renewal, are known to underlie therapeutic resistance in Glioblastoma. Previously, we have shown that treatment with temozolomide (TMZ) initiates remarkable plasticity in glioma cells and promotes the conversion of differentiated glioma cells to GSCs. Our initial investigation indicated that Polycomb group protein EZH2 is critical for this therapy-induced cellular plasticity. We have demonstrated that chemical inhibition and shRNA-mediated knockdown of EZH2 activity prevent the cellular plasticity-mediated conversion of non-GSCs to GSCs. To elucidate the molecular mechanisms by which EZH2 enables cellular plasticity and expands the GSC population after therapy, we performed genome-wide chromatin immunoprecipitation (ChIP) in parallel with DNA sequencing analyses (ChIP-seq) during exposure a patient-derived xenograft (PDX) line to a physiological dose of TMZ (50µM). This ChIP-seq mapping revealed 1449 distinct regions enriched for EZH2 binding. Of these sites, 82% were in intronic regions, 14% occurred in exon areas, and 4% were located in promoter regions. Utilizing pathway Enrichr analysis, we found that post-TMZ EZH2 binding was enriched at the promoter regions of several key genes including PTPRT, CDK5R2, and Siglec6. Gene expression microarray analysis showed that this binding decreased cognate gene expression in an effort to activate the master transcription factor STAT3, a key molecular factor in promoting the GSC niche. Western blot and flow cytometry analysis revealed that, following therapy, EZH2 positive GSCs expressed a higher level of p-(Ser722)-STAT3 (10-fold increase in MFI, p>0.005 ) and p-(Tyr705)-STAT3 (3-fold increase in MFI, p>0.005 ). Given this increase after TMZ, we hypothesized that blocking STAT3 would inhibit chemotherapy resistance in GSCs. Indeed, STAT3 inhibitor sensitized GSCs to TMZ therapy. These findings provide new insight into the molecular mechanisms by which epigenetic plasticity regulates the GSC niche and improve our understanding of how GBM cells resist current treatment modalities.